Researching Global Environmental Politics in the 21st Century - Jennifer Clapp; Peter Dauvergne (Global Environmental Politics, 2016)
This forum article highlights three major research trends we have observed in the journal Global Environmental Politics since 2000. First, research has increasingly focused on specific and formal mechanisms of global environmental governance, contributing to more elaborate and refined methodologies that span more scales and levels of analysis. Second, research increasingly has concentrated on the rise of market-based governance mechanisms and the influence of private actors, reflecting a broader shift among policymakers toward liberal approaches to governance. Third, over this time empirical research has shifted significantly toward analyzing issues through a lens of climate change, providing valuable insights into environmental change, but narrowing the journal’s empirical focus. These trends, which overlap in complex ways, arise partly from shifts in real-world politics, partly from broader shifts in the overall field of global environmental politics (GEP), and partly from the advancing capacity of GEP theories and methodologies to investigate the full complexity of local to global governance. This maturing of GEP scholarship does present challenges for the field, however, including the ability of field-defining journals such as Global Environmental Politics to engage a diversity of critical scholarly voices and to influence policy and activism.